2017
DOI: 10.3390/nu9040384
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Breakfast Skipping and Body Weight, Nutrient Intake, and Metabolic Measures among Participants with Metabolic Syndrome

Abstract: The effect of skipping breakfast on health, especially in adults, remains a controversial topic. A secondary data analysis was conducted to examine associations between breakfast eating patterns and weight loss, nutrient intake, and metabolic parameters among participants with metabolic syndrome (MetS) (n = 240). Three randomly selected 24-h dietary recalls were collected from each participant at baseline and at the one-year visit. Skipped breakfast was seen in 32.9% at baseline and in 17.4% at the one-year vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 52 publications
0
30
0
1
Order By: Relevance
“…Moreover, breakfast skipping was also reported to be associated with a higher prevalence of obesity (7) , hypertension (10,11) , hyperlipidaemia (11,12) , insulin insensitivity and type 2 diabetes (7) and CVD (11,13) . Such reports might partly explain findings from previous crosssectional and intervention studies which show that eating breakfast may be a predictor of healthy eating behaviour, and implies a high intake of dietary fibre, thiamine or folate, and a low intake of fat (14)(15)(16) . A systematic review of studies about breakfast skipping reported that one of the main factors for breakfast skipping was habituation (17) .…”
mentioning
confidence: 78%
“…Moreover, breakfast skipping was also reported to be associated with a higher prevalence of obesity (7) , hypertension (10,11) , hyperlipidaemia (11,12) , insulin insensitivity and type 2 diabetes (7) and CVD (11,13) . Such reports might partly explain findings from previous crosssectional and intervention studies which show that eating breakfast may be a predictor of healthy eating behaviour, and implies a high intake of dietary fibre, thiamine or folate, and a low intake of fat (14)(15)(16) . A systematic review of studies about breakfast skipping reported that one of the main factors for breakfast skipping was habituation (17) .…”
mentioning
confidence: 78%
“…Logistic regression analysis was used to examine the difference in the prevalence of meeting DRIs based on the Low and Middle groups according to the frequency of the home-cooked meal consumption compared with the High group in the crude and adjusted model. Confounding factors considered in the adjusted model were age category (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50), and 51-64 years), occupation (professional/manager, sales/service/clerical, security/transportation/labour, student, housekeeper, and not in paid employment), living alone or not (yes or no), region (Hokkaido/Tohoku, Kanto, Hokuriku/Tokai, Kinki, Shikoku/Chugoku, Kyusyu), current smoker (yes or no) and habitual alcohol drinker (yes or no), which was reported as a factor affecting the frequency of consumption of meals prepared away from home [8,27]. All statistical analyses were performed with SAS statistical software, version 9.4 (SAS Institute Inc., Cary, NC, USA).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we excluded those with missing data on the frequency of eating out and take-away meals (n = 5). We also excluded those who skipped breakfast, lunch, or/and dinner (n = 749), because meal skipping may affect nutrient and food intakes [31,32], and lactating or pregnant women who may have changed their usual dietary habits (n = 84). [33] Thus, the nal participants consisted of 2,221 Japanese adults aged 18-64 years (921 men and 1,300 women).…”
Section: Data Source and Study Populationmentioning
confidence: 99%
“…Breakfast skipping was associated with lower education and incomes, themselves predictors of lower quality diets and impaired health [37]. Many previous studies have pointed to associations between breakfast skipping and unfavorable health outcomes [13,14,[38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%